2004
DOI: 10.1523/jneurosci.1751-04.2004
|View full text |Cite
|
Sign up to set email alerts
|

Lasting Blood-Brain Barrier Disruption Induces Epileptic Focus in the Rat Somatosensory Cortex

Abstract: Perturbations in the integrity of the blood-brain barrier have been reported in both humans and animals under numerous pathological conditions. Although the blood-brain barrier prevents the penetration of many blood constituents into the brain extracellular space, the effect of such perturbations on the brain function and their roles in the pathogenesis of cortical diseases are unknown.In this study we established a model for focal disruption of the blood-brain barrier in the rat cortex by direct application o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

18
402
0
11

Year Published

2009
2009
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 459 publications
(431 citation statements)
references
References 42 publications
18
402
0
11
Order By: Relevance
“…In rat, transient opening of the BBB is sufficient for induction of focal epileptogenesis (Seiffert et al, 2004). BBB lesion is also considered a primary event in human TLE, leading to the extravasation of serum albumin which is taken up by neurons, astrocytes, and microglia (Seiffert et al, 2004;Van Vliet et al, 2007). In contrast, no changes in astrocyte Kir currents were observed in a systemic kainate rat model, 7-16 days following status epilepticus (SE) (Takahashi et al, 2010).…”
Section: Mutations In the Kcnj10 Gene Cause Epilepsymentioning
confidence: 99%
“…In rat, transient opening of the BBB is sufficient for induction of focal epileptogenesis (Seiffert et al, 2004). BBB lesion is also considered a primary event in human TLE, leading to the extravasation of serum albumin which is taken up by neurons, astrocytes, and microglia (Seiffert et al, 2004;Van Vliet et al, 2007). In contrast, no changes in astrocyte Kir currents were observed in a systemic kainate rat model, 7-16 days following status epilepticus (SE) (Takahashi et al, 2010).…”
Section: Mutations In the Kcnj10 Gene Cause Epilepsymentioning
confidence: 99%
“…Experimental evidence also supports a role of intravascular inflammation, often associated with BBB damage, in seizure disorders (Marchi et al, 2007a;Marchi et al, 2009;Seiffert et al, 2004;van Vliet et al, 2007). Recently, the association between circulating immune cells, their interaction with the BBB, and seizure propensity was proposed; leukocyte adhesion was shown to directly support ictogenesis in the pilocarpine model of seizures (Fabene et al, 2008).…”
Section: Blood-brain Barrier Dysfunction In Epilepsy: Experimental Anmentioning
confidence: 90%
“…While large amount of published data support a correlation between occurrence of spontaneous epileptic seizures, seizures and abnormal BBB, direct evidence for the involvement of BBB breakdown in epileptogenesis has been only recently confirmed by the studies, in which opening of the BBB was sufficient to induce delayed epileptiform activity Seiffert et al, 2004).…”
Section: Blood-brain Barrier Dysfunction In Epilepsy: Experimental Anmentioning
confidence: 99%
“…Recently, it was elegantly demonstrated in rats that albumin can act directly on astrocytes, thereby facilitating epileptogenesis 2004, Ivens et al;Van Vliet et al;. It has been shown that direct brain exposure to serum albumin is associated with albumin uptake into astrocytes that is mediated by TGF-R.…”
Section: The Participation Of Albumin In the Activation Of Astrocytesmentioning
confidence: 99%